Sosialisasi Penerapan Paket Wisata Budaya Lokal Sebagai Atraksi Wisata Alternatif Di Desa Huta Tinggi Kabupaten Samosir - Sabam Syahputra Manurung; Merry Moy Mita; Apriliani Lase; Chairiza Azmi; Siti Aisyah; Angelia Putriana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Local cultural tourism in the village has become an increasingly interesting topic in the context of local economic development and preservation of cultural heritage and exotic experiences for tourists. The implementation of this service aims to provide a deeper understanding through socialisation activities in the application of local cultural tour packages as alternative tourist attractions in the Huta Tinggi Tourism village. The method of implementing this service activity is through a one-day seminar with the stages of observation, building communication regarding the willingness of partners, presentation of material, questions and answers and preparation of reports on the programmes that have been carried out. The focus of this socialisation presentation examines the economic impact, cultural preservation, and community participation in tourism development. By presenting tourist attractions that highlight the uniqueness of Huta Tinggi's local traditions, arts and culture, the village can maintain their heritage and encourage a better understanding of their cultural wealth, which is where the importance of this activityties.